(untitled) (Anclajes, 2018)
Over the last decade, studies on masculinities have become a growing field of scholarship in Argentina. This paper provides a preliminary state of the art and critical account of the latest research on the topic. We emphasize the relation of these studies with others on sexual diversity, identifying important ongoing debates and alerting about vacant areas of inquiry. Focusing on an assessment of both fields’ most important contributions, the paper deals with two major sets of disciplines: history, sociology and anthropology on one hand, and literary, cinematographic and cultural studies on the other.